Food loss in Pacific Island Countries: a scoping review of the literature - Christian-Yves Amato-Ali; Viliamu Iese; Gayathri Mekala; Daniela Hidalgo; Hilda Sakiti-Waqa (Frontiers in Sustainable Food Systems)
Food loss and waste pose significant challenges to global food security, economic development, and environmental sustainability. Pacific Island Countries (PICs), with limited resources, being geographically isolated, and vulnerable to climate change, face unique challenges when it comes to the issue of food loss. This scoping review aims to systematically map the literature on food loss in PICs, addressing knowledge gaps and understanding specific methodological aspects. The review utilizes the PRISMA-ScR process to identify, categorize, and synthesize relevant literature, offering a comprehensive overview of the existing evidence. Studies focusing on food loss in PICs published in English from 2011 to 2023 were included. Exclusion criteria considered studies conducted outside PICs, those lacking food loss reduction interventions, and non-peer-reviewed sources. A comprehensive literature search was conducted using the databases of JSTOR, Scopus, Science Direct and Web of Science. A total of 5,787 studies for food loss interventions were identified and out of these only 49 met the inclusion criteria. A notable increase in publications from 2011, with a significant surge in 2018 and 2019, indicate a growing interest on the topic. The review reveals a limited focus on this issue across individual PICs and underscores the need for more localized expertise in the region. The review also highlights critical inefficiencies in PIC food supply chains and the need for more studies outside the common root crop agricultural system. The scoping review identified three thematic categories addressing food loss in PICs, namely., the lack of infrastructure and need for innovative technology for post-harvest management; increased vulnerability to climate change and postharvest risks of newer convenient markets. The findings underscore the need for holistic and context-specific approaches to create resilient and sustainable food systems in the Pacific, providing valuable insights for researchers, policymakers, and practitioners involved in addressing these challenges.